Model Pengajaran Bahasa dengan Pendidikan yang Memanusiakan - Manurung, Rosida Tiurma (Zenit, 2012)
Modern, digitalized, high tech, global era characterized by the development of sciences has transformed human beings into  heartless machines with no sense of humanity and no concerns  of  their environment. Therefore, education should be packed with the perspective of humanism. Education should not be interpreted as a mere class teaching-learning activity; however, it should refer to the various processes and activities that  should be productive; creative; include skills development, personality, integration, and excellence; as well as moral and spiritual reinforcement. Education should be managed and directed with clear objectives in order to develop positive values in learners. Education should be able to create figures with solid and proven character and personality both in the field of science and humanity. Humanizing education is the capablity of producing humans with sense of